Joint decision-making, technology adoption and food security: Evidence from rice varieties in eastern India - Malabayabas, Maria Luz L.; Mishra, Ashok K.; Pede, Valerien O. (Elsevier, 2023)
This study investigates the effect of married couples’ joint decision-making on rice variety selection on rice productivity—a measure of food security. The study uses the 2016 Rice Monitoring Survey and the endogenous switching regression (ESR) method. Results show that rice farms with joint decision-makers (husband and wife) would have higher yields, particularly in households that adopted MRVGen1 (before 1986) rice varieties. Thus, families with joint-decision making have higher food security. Intervention programs for food insecurity should acknowledge and incorporate information regarding the persons responsible for making rice varietal decisions and the characteristics of modern rice varieties to ensure food security.